Molecular signatures and phylogenomic analysis of the genus Burkholderia: proposal for division of this genus into the emended genus Burkholderia containing pathogenic organisms and a new genus Paraburkholderia gen. nov. harboring environmental species - Sawana, Amandeep; Adeolu, Mobolaji; Gupta, Radhey S. (Frontiers in Genetics, 2014)
The genus Burkholderia contains large number of diverse species which are not reliably distinguished by the available biochemical or molecular characteristics. We report here results of detailed phylogenetic and comparative genomic analyses of 45 sequenced species of the genus Burkholderia. In phylogenetic trees based upon concatenated sequences for 21 conserved proteins as well as 16S rRNA gene sequences, Burkholderia species grouped into two major clades. Within these main clades a number of smaller clades were also clearly distinguished. Our comparative analysis of protein sequences from Burkholderia spp. has identified 42 highly specific molecular markers in the form of conserved sequence indels (CSIs) that are uniquely found in different clades of Burkholderia spp. Six of these CSIs are specific for a group of Burkholderia spp. (referred to as Clade I) which contains all clinically relevant members of the genus as well as the phytopathogenic Burkholderia species. The second main clade (Clade II) composed of the environmental Burkholderia species, is also distinguished by 2 of the identified CSIs. Additionally, our work has also identified 3 CSIs that are specific for the Burkholderia cepacia complex, 4 CSIs that are uniquely found in the Burkholderia pseudomallei group, 5 CSIs that are specific for the phytopathogenic Burkholderia spp. and 22 other CSI that distinguish two groups within Clade II. The described molecular markers provide highly specific means for the demarcation of different groups of Burkholderia spp. and for development of novel diagnostic assays for the clinically important members of the group. Based upon the results from different lines of studies, a division of the genus Burkholderia into two genera is proposed. In this new proposal, the emended genus Burkholderia will contain only the clinically relevant and phytopathogenic Burkholderia species, whereas all other Burkholderia spp. are transferred to a new genus Paraburkholderia gen. nov.